Molecular assessment of ammonia- and nitrite-oxidizing bacteria in full-scale activated sludge wastewater treatment plants - Robinson, Kevin (2003)
Nitrification was assessed in two full-scale wastewater treatment plants (WWTPs) over time using molecular methods. Both WWTPs employed a complete-mix suspended growth, aerobic activated sludge process (with biomass recycle) for combined carbon and nitrogen treatment. However, one facility treated primarily municipal wastewater while the other only industrial wastewater. Real time PCR assays were developed to determine copy numbers for total 16S rDNA (a measure of biomass content), the amoA gene (a measure of ammonia-oxidizers), and Nitrospira 16S rDNA gene (a measure of nitrite-oxidizers) in mixed liquor samples.